MODEL MULTILEVEL UNTUK MENENTUKAN FAKTOR YANG MEMPENGARUHI ANGKA KEMATIAN BAYI - Ainun Mardia; vinny yuliani; Zawaqi Afdal Jamil (Mathematical Sciences and Applications Journal, 2020)
Infant mortality in Indonesia is a very worrying situation. There are so many factors that affect infant mortality in Indonesia. Broadly speaking, the factors that influence infant mortality in Indonesia are divided into two, namely endogenous and exogenous. Data on infant mortality is taken from Ministry of Health data. The data consists of 65 districts in Indonesia and 33 provinces in Indonesia. Data on infant mortality in Indonesia will be modeled using multilevel modeling with level one in the model being the district and level two in the model being the province in Indonesia.Multilevel modeling is structured hierarchical modeling. Multilevel modeling can analyze structured or stratified data. The results obtained from multilevel modeling for factors affecting infant mortality are that the variance in the province becomes greater when the district structure has been released in the model. This indicates that diversity within districts is only influenced by provincial diversity.Abstract is filled with 150-250 words in Indonesian. Written in Times New Roman font style and font size 12, space 1. Abstract content is a summary of the problem and purpose, research methods, results and conclusions. Keywords: Babies Modeling, Mortality, Multilevel, Statistics